2019
DOI: 10.1186/s41936-019-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of triclosan impact on enzymatic biomarkers in an Indian major carp, Catla catla

Abstract: Background: The present study was designed to determine the median lethal concentration (96-h LC50) of triclosan (TCS) and to investigate the effect of a sublethal concentrations of TCS on the activities of glutamic oxaloacetic transaminases (GOT), glutamic pyruvic transaminases (GPT), and glutathione S-transferase (GST) in the gill, liver, and muscle of an Indian major carp Catla catla. Results: In this study, static renewal procedure was followed to determine the 96 LC50 value. The results indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Authors reported that sublethal concentrations of triclosan upon subchronic exposure significantly decreased SOD, CAT, GPx, GSH, and GSSH in the liver of adult zebrafish, and simultaneously caused dose-dependent DNA damage in hepatocytes. Following triclosan exposure, Hemalatha et al ( 2019 ) noticed significantly enhanced glutamic oxaloacetic transaminases (GOT), glutamic pyruvic transaminases (GPT), and GST activity in the liver of Indian major carp Catla catla in a dose- and time-dependent manner. Except for triclosan, there are other antimicrobials often found in PCPs (triclocarban, biphenylol, chlorophene, bromophene, etc.…”
Section: Wwtp-associated Legacy Contaminants and Emerging-concern Con...mentioning
confidence: 99%
“…Authors reported that sublethal concentrations of triclosan upon subchronic exposure significantly decreased SOD, CAT, GPx, GSH, and GSSH in the liver of adult zebrafish, and simultaneously caused dose-dependent DNA damage in hepatocytes. Following triclosan exposure, Hemalatha et al ( 2019 ) noticed significantly enhanced glutamic oxaloacetic transaminases (GOT), glutamic pyruvic transaminases (GPT), and GST activity in the liver of Indian major carp Catla catla in a dose- and time-dependent manner. Except for triclosan, there are other antimicrobials often found in PCPs (triclocarban, biphenylol, chlorophene, bromophene, etc.…”
Section: Wwtp-associated Legacy Contaminants and Emerging-concern Con...mentioning
confidence: 99%
“…A recent study on mosquitofish ( Gambusia affinis ) that were exposed to TCS showed that the up-regulations Sirt1 and Sirt2 in Sirtuin family could activate the Nrf2/ARE signaling pathway and the down-regulations of miR-34b and the up-regulations of miR-34a , miR-144, and miR153a-5p modulated the Nrf2/ARE signaling pathway [ 234 ]. Sublethal concentrations of TCS enhanced glutamic oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), and glutathione-S-transferase enzyme activity in all the tissues with an increased dose and exposure period in the gill, liver, and muscle of an Indian major carp Catla catla [ 235 ]. Studies on the fly Drosophila melanogaster showed that TCS caused a redox imbalance with an increase on the catalase activity and a decrease on reactive oxygen species (ROS) level [ 236 ].…”
Section: Mechanism Of Action In Pharmacological and Toxicity Studiesmentioning
confidence: 99%
“…Toxicity studies conducted on various organisms proved that TCS is acutely and chronically toxic to all the organisms especially to the aquatic organism through wastewaters from different sources. Earlier studies observed the median lethal concentration (LC 50 ) of TCS on different fishes as 4400 µg.l -1 in Onchorynchus mykiss (Adolfsson- Erici et al, 2002), 370 and 1700 µg.l -1 in Oryzias latipes (Orvos et al, 2002 andNassef et al, 2009), 340 µg.l -1 in Danio rerio (Oliviera et al, 2009), 1480 µg.l -1 in Xiphophorus helleri (Liang et al, 2013), 2810 µg.l -1 in Oreochromis niloticus (Vijitha et al, 2017), 1458 µg.l -1 in Pangasianodon hypophthalmus (Sahu et al, 2018), 1767 µg.l -1 in Anabas testudineus (Priyatha and Chitra, 2018), 360 µg.l -1 in Gibelion catla and 390 µg.l -1 in Labeo rohita (Hemalatha et al, 2019a and2019b). In the present study, the LC 50 value of TCS on O. mossambicus was calculated based on the 96 h mortality data of fishes exposed to TCS.…”
Section: Determination Of Lc 50 and Behavioural Responsesmentioning
confidence: 99%